Effect of circumferential air-splint pressure on the soleus stretch reflex during a voluntary ramp plantar flexion - Agostinucci, J. (Нейрофизиология, 2010)
Circumferential pressure (CP) applied to the limb has been shown to decrease muscle activity in subjects without neuromuscular disorders and in individuals with a spinal cord injury and cerebrovascular accidents. Було показано, що круговий тиск (КТ), прикладений до кінцівки, зумовлює зменшення м’язової активності в осіб без нервово-м’язових розладів і у пацієнтів з пошкодженнями спинного мозку й цереброваскулярними патологіями.